Keluar Dari “Teks Besar” Gagasan Post-Positivist dalam Studi Hubungan Internasional - Ade Marup Wirasenjaya (Universitas Muhammadiyah Yogyakarta, 2012)
The emergence of new perspectives in the International relations study is driven by analysis unit studies which experience a fundamental change in the world of interdependency today. The old unit analysis, which emphasized “great actor” and formal started to be sued. International relations are characterized by the presence of International society which includes issues, actor also new pattern relation which very influences the explanation and description of International relations. Hierarchy of International relations has been yielding to the external problems and internal problems blurred. Post-positivist view of descent proposed as a new analytical tool in International relations which changed drastically.